Detection of a prfA-independent promoter responsible for listeriolysin gene expression in mutant Listeria monocytogenes strains lacking the PrfA regulator. - Domann, E (1993)
Expression of listeriolysin, a major virulence factor of pathogenic Listeria monocytogenes, is positively regulated by the pleiotropic virulence regulator PrfA. In this study, we demonstrate that L. monocytogenes strains lacking the prfA regulator gene produce listeriolysin in small, albeit detectable, amounts when analyzed in a hemolysin assay and by immunoblots with listeriolysin-specific monoclonal antibodies. Transcriptional analysis revealed the existence of a PrfA-independent promoter that was responsible for the hemolytic activity expressed by these strains.